Epratuzumab for the treatment of systemic lupus erythematosus. (3rd April 2018) - Geh, Daniel; Gordon, Caroline
ABSTRACT: Introduction : Systemic lupus erythematosus (SLE) is a multi-system autoimmune disease. There are three drugs licensed for the treatment of lupus: corticosteroids, hydroxychloroquine and belimumab. Immunosuppressants such as azathioprine, methotrexate and mycophenolate are also used. Despite these treatments there is still considerable morbidity. New treatments are needed for the management of active lupus. Epratuzumab a humanized IgG1 monoclonal antibody that targets CD22 resulting in selective B cell modulation that has been considered a potential treatment for SLE. Areas covered : Summary of the relevant pathogenesis and disease activity measurements used in SLE patients, current treatments and unmet needs in SLE, pharmacokinetics and pharmacodynamics of epratuzumab therapy, and a summary of the 7 clinical trials that have investigated the efficacy and safety of epratuzumab in SLE. Expert commentary : It is not clear why trials have failed to demonstrate efficacy but high placebo response rates from optimisation of standard of care and a sub-optimal dosing regimen may have played a role. Post-hoc analysis suggested that there may be subgroups that did respond, such as anti-SSA positive patients with features of Sjogren's syndrome. Further research is needed to explore this and other potential sub-groups that might respond.